2018
DOI: 10.1073/pnas.1800123115
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio spectroscopy and ionic conductivity of water under Earth mantle conditions

Abstract: The phase diagram of water at extreme conditions plays a critical role in Earth and planetary science, yet remains poorly understood. Here we report a first-principles investigation of the liquid at high temperature, between 11 GPa and 20 GPa-a region where numerous controversial results have been reported over the past three decades. Our results are consistent with the recent estimates of the water melting line below 1,000 K and show that on the 1,000-K isotherm the liquid is rapidly dissociating and recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…Simulations of electric properties, such as ionic conductivity, necessitate long timescales and, except for cases at extreme conditions 16 , are normally beyond reach of density functional theorybased MD. One way to tackle this time-scale challenge is to explore finite-field methods to speed up the convergence of the polarization P, which has been successfully applied to compute the dielectric constant of polar liquids and the capacitance of electrified solid-electrolyte interfaces 17 .…”
mentioning
confidence: 99%
“…Simulations of electric properties, such as ionic conductivity, necessitate long timescales and, except for cases at extreme conditions 16 , are normally beyond reach of density functional theorybased MD. One way to tackle this time-scale challenge is to explore finite-field methods to speed up the convergence of the polarization P, which has been successfully applied to compute the dielectric constant of polar liquids and the capacitance of electrified solid-electrolyte interfaces 17 .…”
mentioning
confidence: 99%
“…It has been reported that generalized gradient approximations (GGAs) may not be able to describe doubly charged anions in water accurately at ambient conditions [35]. However, PBE performs better at HP-HT conditions than at ambient conditions, as shown in many of our previous studies [14,[22][23][24]. Our previous finding that CO 2 (aq) is absent at ∼11…”
Section: Molecular Geometry Of H 2 Comentioning
confidence: 61%
“…Our total simulation time exceeds 3.8 nanoseconds. We found that at ∼10 GPa and 1000 K, [22], dielectric constant [23], Raman and IR spectra, and ionic conductivity [24], as well as the reactions of CO 2 and carbonates in HP-HT water [14].…”
Section: Introductionmentioning
confidence: 80%
“…This observation cannot be explained by the increased self-dissociation of water, which increases with pressure (see e.g. Rozsa et al (2018); Goncharov et al (2005)). According to Marshall and Franck (1981) the OH − molality is in the range of 10 -6 to 10 -5 under the investigated P/T conditions.…”
Section: Thermodynamic Datamentioning
confidence: 99%